Konsep Kepemimpinan Islam Perspektif Kuntowijoyo dengan Pendekatan Profetik - Haikal, Fikri; Syahrusi, Mutiara; Febriany, Dinda Ayu; Fadhilah, Mellisa Nur; Akhmad, Fandi (Lembaga Yasin AlSys, 2022)
This research is motivated by the nature of humans being created, namely as caliphs on earth or as leaders. In this connection, humans are expected to be able to become leaders for themselves, others and the universe in regulating, managing, and contributing to all the potential that is qualified in their leadership as leaders. Leadership is someone who can influence, encourage, invite, guide, and move others to achieve common goals. In the context of Indonesia today, leadership is needed that is able to embrace, free from poverty, ignorance and the marginalized. Leaders who are based on humanity and lead to the teachings of their religion. Various references, there are lots of leadership models, but according to researchers with historical conditions and the dielectics of Indonesia's structural structure, the right leader is a leadership model that has characteristics with a prophetic approach. The purpose of this study was to analyze the understanding, characteristics, and concepts of leadership in the Islamic perspective of Kuntowijoyo with his prophetic approach. This research uses library research method. To obtain objective and up-to-date data, researchers collect data through books by Kuntowijoyo, journals, and published scientific research results. From the results of this study, it can be explained that the concept of leadership in Islam is a perspective that forms the basis for thinking in the role of being a leader with his leadership model. The concepts possessed by Islamic teachings in viewing the concept of leadership include aspects of influence, spirituality, and characteristics. In Kuntowijoyo's perspective, the prophetic approach has values, namely liberation, humanization and transcendence.